A phenomenological analysis of young male prisoners’ experiences of trauma: 'Trauma is every day' - O'Rourke, Rachel (International journal of law, crime and justice, 2025)
This study explores the impact of trauma for 18-25-year-old men in a UK prison serving long sentences of more than 10 years, considering whether their offence and sentence length are part of that trauma, and exploring coping responses. Qualitative methodology (Interpretative Phenomenological Analysis: IPA) was used to analyse 9 semi-structured interviews with young men, discussing their experiences in their own terms. The experiences were organised into three overarching themes, 1. 'Conceptual Confusion', 2. The 'Impact Now of Trauma' and 3. 'Settling'. The study demonstrated that it is possible to discuss the concept of difficult life events with young adult male prisoners, though more difficult for some participants than others. The study supports existing concepts around the experience of trauma in young men, adding insights into the challenges to assessment and intervention work with this cohort, including avoiding assumptions of age-related homogeneity, and ideas for what might be helpful to these men whilst in prison.